E0575 B-type natriuretic peptide on coronary circulation in York pigs model of acute myocardial infarction with heart failure. (17th November 2010) - Zhang, Jing; Fu, Xianghua; Wang, Qingsheng; Fan, Xinna; Wang, Yanbo; Wang, Xuechao
Abstract : Objective: To evaluate the impact of intravenous administration of rhBNP on coronary artery haemodynamics in York pigs model of AMI-HF. Methods: Total of 14 York pigs were included in this study. The AMI-HF models was made by coronary occlusion and microthrombi perfusion, pigs were randmised into saline group and rhBNP group. Administration of rhBNP (bolus of 1.5 μg/kg followed by a continuous infusion of 0.01 μg·kg −1 ·min −1 for 60 min, and then the dosage can be increased to 0.02–0.03 μg·kg −1 ·min −1 until LVEDP<12 mm Hg, maintaining MBP≥65 mm Hg) in rhBNP group. The saline group was given equal volume of normal saline using the same method. Coronary pressure (Pc ), the average peak velocity (APV), coronary vascular resistance (CR), coronary flow reserve (CFR) and coronary diameter were recorded simultaneously at baseline, instant after the model established, 60min after continuous infusion of 0.01 μg·kg −1 ·min −1 rhBNP and the time point of LVEDP<12 mm Hg. The coronary blood flow was measured at rest and maximal hyperaemia. Results: 12 animals achieved the standard of AMI-HF model successfully, the observation parameters were recorded at baseline before balloon occlusion, instant after the model established, 60min after continuous infusion of 0.01 μg·kg −1 ·min −1 rhBNP and the time point of LVEDP decreased to <12 mm Hg. 1. Changes of Coronary artery parameters: There is no significant difference of coronary diameter, APV, CR and CFR in saline group. Coronary artery diameter increased after rhBNP administration. According to the intracoronary Doppler flow results, APV and CBF were significantly increased and CR decreased after rhBNP administration. CFR was significant rebound after continuous infusion of 0.01 μg·kg −1 ·min −1 rhBNP for 30 min. And compared with the control group at the same observation point, APV and CBF significantly increased and CR significantly decreased at the stage of infusion 0.010 μg·kg −1 ·min −1 Doppler parameters of renal artery, there was no difference of rhBNP. LVEF measured by echocardiography was lower than baseline after the models established and tended to increase after administration of rhBNP, but no significance was found compared with that in saline Group and that immediate after models established. Conclusion: It could increase blood flow of injury coronary artery, improve CFR and improve the coronary and administration of rhBNP in pigs with AMI-HF.